METHODS CONTROL RADIOASTRONOMY OBSERVATIONS AND PROCESSING OF COSMIC RADIO SOURCES - Isaev, E. A. (Одеські астрономічні публікації, 2012)
In this paper the following methods represented: control of the radio astronomical observations using the estimation results, making decisions on the detection of cosmic sources, taking into account noise and interference, and recognizers classes of cosmic radio sources to the maximum of a posteriori probability (Bayesian approach). The problem researched is about storing and transferring large amounts of scientific information from cosmic radio sources to consumers.